Pengaruh Model Teams Games Tournament Berbantu Media Ethno-Puzzle terhadap Pemahaman Konsep IPA Siswa Kelas V - Nurwulan, Devi Ayuk; Ardianti, Sekar Dwi; Fajrie, Nur (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to analyze the effect of applying the Teams Games Tournament (TGT) learning model assisted by Ethno-Puzzle media in understanding the science concept of fifth grade students at SDN Clering 01 Jepara. This study used a quantitative experimental research design, namely the one group pretest-posttest design. This design is a pre-experimental development with data collection obtained from observation, concept understanding tests and documentation. The place of this research will be carried out in class V SD Clering. The sample in this study were 20 students using a saturated sampling technique. The results of this study indicate that the statistical score of the paired sample t test shows that there is a difference in the pretest average value of 54 while the posttest average value is 81.10 and the Paired Sample T-Test hypothesis test score with Stg. (2-tailed) i.e. 0.000 <0.05, then Ho is rejected and Ha is accepted so that the Teams Game Tournament (TGT) assisted by Ethno-Puzzle media influences the understanding of the concept of science in fifth grade students at SDN Clering 01 Jepara.